Simultaneous occurrence of the North Atlantic Seesaw and El Niño - I. Méndez Ramírez (Atmósfera, 2007)
Models of dichotomic and polytomic logistic regression are applied to series of historical records spanningone and a half centuries (1840-1990) of the North Atlantic Seesaw (NAS) and El Niño (EN), looking forsimultaneous occurrence of both phenomena during the northern winter months and classifying NAS in fourmodalities and EN in three intensities. NAS refers to the temperature anomalies in Greenland and Norway; itsmodalities are: both positive (BA), both negative (BB), Greenland positive with Norway negative (GA) andGreenland negative with Norway positive (GB). A bigger incidence of NAS is found as winter progresses, aswell as simultaneity of occurrence of 61% between the NAS and EN. NAS heterogeneous modalities (GA andGB) coincide in 71% with EN events, while homogeneous modalities (BA and BB) do so in 29%. Heterogeneousmodalities have a higher coincidence with EN greatest intensity (3). When the frequencies computed throughthe logistic polytomic model were compared to the observed frequencies, a very close goodness of fit wasfound, when the whole winter season was considered